2016
DOI: 10.3758/s13414-016-1135-2
|View full text |Cite
|
Sign up to set email alerts
|

Value-modulated oculomotor capture by task-irrelevant stimuli is a consequence of early competition on the saccade map

Abstract: Recent research has shown that reward learning can modulate oculomotor and attentional capture by physically salient and task-irrelevant distractor stimuli, even when directing gaze to those stimuli is directly counterproductive to receiving reward. This value-modulated oculomotor capture effect may reflect biased competition in the oculomotor system, such that the relationship between a stimulus feature and reward enhances that feature's representation on an internal priority map. However, it is also possible… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

18
114
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 66 publications
(133 citation statements)
references
References 47 publications
18
114
1
Order By: Relevance
“…Pairing a stimulus with reward is thought to increase its attentional priority in a way that mimics or otherwise interacts with its physical salience. For example, eye-tracking studies have demonstrated that VMAC is largest for the most rapidly generated saccades, and diminishes with increasing saccade latency (Failing, Nissens, Pearson, Le Pelley, & Theeuwes, 2015;Pearson et al, 2016), a pattern similar to that observed in capture by physical salience (e.g., van Zoest, Donk, & Theeuwes, 2004). Similarly, neuroimaging and electrophysiological studies have shown that the influence of reward arises early on in visual processing, with reward effects observed as early as low-level visual cortex (e.g., MacLean & Giesbrecht, 2015;Serences, 2008;Serences & Saproo, 2010).…”
Section: The Role Of Selection History In Guiding Attentionmentioning
confidence: 73%
See 2 more Smart Citations
“…Pairing a stimulus with reward is thought to increase its attentional priority in a way that mimics or otherwise interacts with its physical salience. For example, eye-tracking studies have demonstrated that VMAC is largest for the most rapidly generated saccades, and diminishes with increasing saccade latency (Failing, Nissens, Pearson, Le Pelley, & Theeuwes, 2015;Pearson et al, 2016), a pattern similar to that observed in capture by physical salience (e.g., van Zoest, Donk, & Theeuwes, 2004). Similarly, neuroimaging and electrophysiological studies have shown that the influence of reward arises early on in visual processing, with reward effects observed as early as low-level visual cortex (e.g., MacLean & Giesbrecht, 2015;Serences, 2008;Serences & Saproo, 2010).…”
Section: The Role Of Selection History In Guiding Attentionmentioning
confidence: 73%
“…Consistent with previous VMAC protocols ( Le Pelley et al, 2015;Pearson et al, 2015Pearson et al, , 2016, participants completed a brief questionnaire after finishing the visual search task, to assess their knowledge of the colour-reward contingencies, and of the omission contingency (i.e., that looking at the coloured distractor caused omission of reward). Participants were presented with an orange and blue circle, in random order, and for each were asked to indicate whether they would earn 0 points, 10 points, or 500 points when the display contained a circle of that colour and they (1) moved their eyes quickly and accurately to the target, or (2) looked at the coloured shape before looking at the diamond.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The reduced overall accuracy and faster RTs in the present study compared to Sha and Jiang (2016) attests to the added difficulty associated with this design feature, which was employed in the original demonstration of value-driven attentional capture (Anderson et al, 2011b) and has been subsequently adopted in many other implementations of the paradigm. In the oculomotor capture literature, attentional capture is most prominent on fast response trials (e.g., van Zoest, Donk, & Theeuwes, 2004), including in the case of value-driven attentional capture (Pearson et al, 2016). For studies looking to measure value-dependence, implementing this design feature may be advantageous.…”
Section: Discussionmentioning
confidence: 99%
“…This contrasts with a single-phase approach involving task-irrelevant but reward-predictive distractors (Le Pelley et al, 2015), which by their predictive nature possess some degree of relevance, pertinence, or informational value. In the typical implementation of the single-phase paradigm, the distractors are also physically salient, pairing reward with a corresponding automatic orienting response and confounding salience-dependent effects with value-dependent effects (e.g., Bucker, Belopolsky, & Theeuwes, 2015; Le Pelley et al, 2015; Pearson et al, 2015, 2016); when the distractors are non-salient, it appears that participants need to be explicitly informed of the relationship between reward and color, further suggesting that actively monitoring for reward-predictive information may play a role (Failing, Nissens, Pearson, Le Pelley, & Theeuwes, 2015; see also Munneke, Belopolsky, & Theeuwes, 2016). …”
Section: Discussionmentioning
confidence: 99%